Supraspinatus tendinosis and elite swimming training - Sein, M.; Walton, J.; Linklater, J.; Appleyard, R.; Kuah, D.; Kirkbride, B.; Murrell, G. (Australian conference of science and medicine in sport 2004. Hot topics from the Red Centre, 2004)
Supraspinatus tendinopathy is a common cause of shoulder pain in swimmers. Recent laboratory studies have shown that tendinopathy may relate to the magnitude and frequency of load to tendon cells. The purpose of this study was to determine to what extent, if any, training characteristics were associated with supraspinatus tendinopathy in elite swimmers. Under ethics approval, 24 elite swimmers (state-international levels) with an age range of 14-32 years completed a questionnaire regarding their training regimes (numbers of years coached, hours per week in swimming training, level of competition, distance swum per week and stroke specialty) and had magnetic resonance imaging using oblique coronal proton density (PD) and fat suppressed T2, sagittal T2 axial PD and fat suppressed PD sequencing performed on a Signa 1.5 T MRI unit. 18/24 swimmers were found to have supraspinatus tendinosis. Pearson`s product moment correlation revealed a statistically significant relationship (p<0.05) between hours spent training each week and tendinopathy. Multiple logistic regression analysis was performed with tendinopathy as the dependent variable and training regime parameters as independent variables. No correlation was found between specific types of swimming stroke and the presence of tendinopathy. However, we did confirm that the number of training hours per week positively correlated with tendinopathy whereas level of competition, years of training, and distance swum per week did not. An equation was generated which correctly predicted that 79% of the athletes who trained for over 15 hours per week were more likely to develop tendinopathy than those who trained for less time.